Effects of Timeliness on the Trade Pattern between Primary and Processed Goods - Baniya, Suprabha (Washington, D.C. : International Monetary Fund, 2017)
This paper investigates the effect of timeliness in accessing the intermediate inputs on the trade pattern. In particular, any country that has a higher ability to transport goods on time has a comparative advantage in industries that place a higher value on the timely delivery of their inputs, and this comparative advantage pattern is stronger for processed goods than for primary goods. To do this, a measure for how intensively any industry demands for the timely delivery of its intermediate inputs is constructed combining Hummels and Schaur (2013)'s calculations of the time sensitivity of products with the input-output tables.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet